2018
DOI: 10.1039/c7cy02466e
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the nature of the support on the catalytic performance of CALB: experimental and theoretical evidence

Abstract: CALB immobilized on hydrophobic supports exhibits higher conversion of ibuprofen and enantiomeric excess towards the S-enantiomer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…In the same way as for physical adsorption, both hydrophilic and hydrophobic supports can be used for covalent immobilization. 97 Jose et al 97 reported the use of functionalized chitosan, epoxy acrylic resin, and functionalized magnetite as supports for Candida antarctica lipase B covalent immobilization with subsequent application in the esterification of R/S-ibuprofen with ethanol. Another technique of immobilization was employed as well as other supports, but some decrease in the specific activity was observed in those immobilized by covalent bonding.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…In the same way as for physical adsorption, both hydrophilic and hydrophobic supports can be used for covalent immobilization. 97 Jose et al 97 reported the use of functionalized chitosan, epoxy acrylic resin, and functionalized magnetite as supports for Candida antarctica lipase B covalent immobilization with subsequent application in the esterification of R/S-ibuprofen with ethanol. Another technique of immobilization was employed as well as other supports, but some decrease in the specific activity was observed in those immobilized by covalent bonding.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…5,6 The supporting materials should meet the demands for biocompatibility, stability, and high enzyme loadings. 7,8 Recently, graphene oxide (GO) has attracted wide attention due to its incredibly large specific surface area (single-layered and unique double-sided material), abundant oxygen-containing functional groups (such as hydroxyl, carbonyl, carboxyl, and epoxy groups), and high biocompatibility. 9,10 These unique physical and chemical properties make GO an outstanding supporting matrix for enzyme immobilization.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of CALB, there is an immobilized commercial preparation supplied by Novozymes, Novozym ® 435, immobilized on a macroporous acrylic polymer resin (Lewatit VP OC 1600) [33]. This biocatalyst has been successfully used in diverse reactions, but it has been described to possess some limitations, like enzyme release in certain media, polymer dissolution in organic media, or the capture of hydrophilic compounds in the enzyme environment [33,34,35,36,37,38,39]. Thus, an alternative support may further increase the implementation of these interesting enzymes.…”
Section: Introductionmentioning
confidence: 99%